Traumatic hallux sesamoid fracture: a case report - Demasi Quadros de Macedo, Gustavo; Saori Gushiken, Erika; de Oliveira, Gabriel Hernandes; Vasconcelos de Castro, Larissa; Farias Molina, Wellington (Journal of the Foot & Ankle, 2022)
The authors describe an extremely rare case of traumatic fracture of both hallux sesamoid bones, which was treated non-surgically, and the indications, contraindications, and unfavorable outcomes analyzed. Level of Evidence V; Therapeutic Studies; Expert Opinion.